1995
DOI: 10.1523/jneurosci.15-12-07879.1995
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 increases Otx2 expression in precursor cells from mammalian telencephalon

Abstract: Dissociated primary cultures from rat telencephalon at different developmental stages were used to study the effect of basic fibroblast growth factor (FGF2) on Otx2, Dlx1, and Emx1, three homeobox genes expressed in different regions of the developing mammalian forebrain. At embryonic day (E)13.5. the regional pattern of expression of Otx1, Otx2, Dlx1, Dlx2, Dlx5, and Emx1 is maintained in primary culture, suggesting that cells are already committed to a regional identity at this stage. In these cultures, Otx2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In addition to its ventralizing effect, Shh can exert a proliferative effect on NPCs (Lai et al, 2003), and accordingly we observed a decrease in the proliferation and survival of NPCs in the presence of cyclopamine. To mitigate this loss of viability, the mitogen FGF-2, also known to exert an instructive role during telencephalic development (Ideguchi et al, 2010; Paek et al, 2009; Robel et al, 1995), was added and found to reverse the impact of cyclopamine on cell survival and proliferation (data not shown). This approach (Figure 1A) first converted hESC cultures to a neural lineage at a high rate, as determined by nestin and Pax6 expression (Figure 1B, C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its ventralizing effect, Shh can exert a proliferative effect on NPCs (Lai et al, 2003), and accordingly we observed a decrease in the proliferation and survival of NPCs in the presence of cyclopamine. To mitigate this loss of viability, the mitogen FGF-2, also known to exert an instructive role during telencephalic development (Ideguchi et al, 2010; Paek et al, 2009; Robel et al, 1995), was added and found to reverse the impact of cyclopamine on cell survival and proliferation (data not shown). This approach (Figure 1A) first converted hESC cultures to a neural lineage at a high rate, as determined by nestin and Pax6 expression (Figure 1B, C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FGF-2 exerts a wide range of activities during early brain development, including stimulation of neural precursor proliferation, neuronal differentiation, neurite outgrowth of hippocampal and cortical neurons, and enhancement of neuronal survival (Gremo and Presta, 2000). FGF-2 may also play a role in forebrain patterning, as it has been suggested to regulate Otx2 expression in the developing telencephalon (Robel et al, 1995). In contrast to the previous studies of ESC cortical differentiation (Gaspard et al, 2008; Shi et al, 2012), we found that FGF-2 could be used to greatly enhance forebrain NPC survival and proliferation, as well as promote a downstream increase in the number of human cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for PCR amplification of Emx-1 and Dlx-2 were designed based on the published sequences of the rat cDNAs (26). The Emx-1 forward primer (nucleotides 10 -31) was 5Ј-CCTGGCTGGCTGGGTG-CACACC-3Ј, and the reverse primer (nucleotides 278 -289) was 5Ј-CCACTCACGAAGGCCGCCTCG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Oligonucleotide (Operon Technologies, Alameda, CA) probe sequences were based on rat cDNAs (Robel et al, 1995), and were as follows: Otx-1 5Ј-CAT GGG GCT AAG CTG GTG CGG GTG GTG ATG AGA GTG CAT GGG-3Ј Otx-2 5Ј-AAG ATC CAC AGT CCA TGC CCC CAA AGT AGG AAG TCG AGC CAG-3Ј. Oligonucleotides were purified through NAP-10 columns (Pharmacia, Piscataway, NJ).…”
Section: Otx-1 and 2 Oligonucleotidesmentioning
confidence: 99%